Coordinative intra-segment indicators of karate performance - Goethel, Marcio Fagundes; Ervilha, Ulysses Fernandes; Vieira, Pedro [UNESP]; Moreira, Sarmet; Silva, Venicius de Paula; Bendillati, Antonio Roberto [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Goncalves, Mauro [UNESP] (Int Scientific Information, Inc, 2019)
Background and Study Aim: Whether from the lower or upper limbs, intersegmental coordination is required at a high level in the blows of various martial arts modalities, with karate being no exception. In karate, precision, high speed, and technique are the hallmarks of attack, counterattack, and defence. The aim of this study was the phase relationship between the proximal and distal joints during the execution of two technique of stroke karate: the punch gyaku tsuki and the kick me geri. Material and Methods: The study included 14 male athletes, equally divided into 2 subgroups according to their current competitive level: sub-elite (SEG) and elite (EG). The karate stroke performance measure used was the linear velocity peak of the wrist and foot. In order to analyze the intra-segment coordination, it was applied the nonlinear dynamics approach named continuous relative phase (CRP). From the CRP curve it was obtained the peak as well as the time to reach the CRP peak. It was also compared the index of the coordinative patterns' variability, which was obtained by calculating the average of the CRP values and standard deviation. Results: The EG group showed significantly higher values in the linear velocity peak of the wrist and foot when compared to the SEG. With respect to the CRP curve peak and the coordinative patterns variability, the SEG group presented significantly higher values, showing no differences in the time to reach the CRP peak. Conclusions: The EG group presented a better intra-segment coordinative capacity during the execution of strikes. The stability of coordinative patterns seems to have an intimate relationship with the technical refinement. Thus, this variable can be configured also as a predictor of performance.
Keywords: gyaku tsuki; horizontal axis; mae geri; nonlinear dynamics; vertical axis